Development of Edutainment-Based Mathematics Learning Media on Social Arithmetic Materials - Pratiwi, Shanty Hanna; Panggabean, Suvriadi (Lembaga Riset Mutiara Akbar, 2022)
This study is research on the development of edutainment-based mathematics learning media on social arithmetic material at the seventh-grade junior high school level and using macromedia flash 8. The purpose of this study was to determine how the development of edutainment-based learning media at the seventh-grade junior high school level, and how appropriate the learning media was. edutainment-based mathematics in mathematics learning, as well as to determine the responses and interest of students to the development of edutainment-based learning media at the seventh-grade junior high school level. The development model used in this study is the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. In the implementation stage, the researcher limited the trial to a small scale with 15 students. The results of this study obtained a validation level of 90% by material experts, 91% by media experts, 82.4% of students expressed interest, which means that the development of edutainment-based mathematics learning media is feasible and valid as a mathematics learning media.